Charting the aquaculture internet of things impact: key applications, challenges, and future trend - Abdullah, Ahmad Fikri; Che Man, Hasfalina; Mohammed, Abdulsalam; Abd Karim, Murni Marlina (Elsevier, 2024)
Aquaculture plays a pivotal role in global food production, grappling with distinct hurdles linked to the oversight of water quality, feeding procedures, and disease control. Efficient management of these core aquaculture operations has been acknowledged as a fundamental measure, yet remains unattainable through traditional methodologies. The advent of the Internet of Things (IoT) has opened up transformative avenues for real-time aquaculture operations. IoT solutions have emerged as a potent toolset, facilitating prompt monitoring, data collection, analysis, and control within aquatic environments. Notwithstanding its remarkable advantages, the technology is not devoid of limitations and areas requiring advancement. This paper critically examines the diverse applications of IoT in aquaculture, encompassing water quality monitoring, optimized feeding strategies, and intelligent health inspection. The challenges associated with aquaculture operations, such as sensor vulnerability to corrosion, limitations concerning data fusion, environmental influences on data transmission, and other pertinent issues, have been thoroughly discussed. Additionally, it also reports the promising prospects of IoT, highlighting advancements in sensor technology, integration with artificial intelligence and machine learning, and the potential for amplified productivity within the aquaculture sector. By presenting the dynamic landscape of IoT in aquaculture, this paper underscores its remarkable potential in addressing critical challenges, while emphasizing the necessity for a balanced approach to mitigate drawbacks.